Chlamydia in adolescent/adult reproductive management trial study (CHARM): Clinical core protocol - Mark, Katrina S. (Contemp Clin Trials Commun, 2019)
INTRODUCTION: Chlamydia trachomatis (CT) is a common sexually transmitted pathogen with significant reproductive health implications. Data are mounting that the bacterial communities that reside within the vagina, collectively termed the vaginal microbiota, aid in defense against sexually transmitted infections. Disruptions in the vaginal microbiota, such as during episodes of bacterial vaginosis, may increase susceptibility to infection. Herein, we describe the clinical core protocol for a NIH NIAID Cooperative Research Center titled Eco-Pathogenomic of Chlamydial Reproductive Tract Infection. The primary goals of the project are to describe the interrelationships between the urogenital microenvironment, the properties of the pathogen and immunologic responses of the host in men and women, and their association with clinical outcomes of CT infection in women. METHODS: Men and women with confirmed genital CT infections were recruited to a number of study protocols, including cross-sectional and longitudinal sub-studies. Participants completed a demographic and sexual health questionnaire and underwent a physical exam at baseline. In the longitudinal study arms, biologic samples were collected daily, weekly, and monthly to determine the relationships between the vaginal microbiota, prevalent CT infection, re-infection and treatment. DISCUSSION: The biological samples and the demographic and history information collected throughout this study will be used for various analyses evaluating genomics, metabolomics and host immune responses in the context of CT infection.